The "Real World" Aspirations of Work-Bound Rural Students - Beverly A. Burnell (Journal of Research in Rural Education, 2003)
Twenty-six work-hound. college-able. rural high school seniors were interviewed regarding their post-high school aspirations. their dews 0/the transitions associated with leaving high school. and the processes by which they came to think ofthemselves as work-hound. One ofseveral emergent themes is presented: students "perspectives ofthe real world and how these perspectives have influenced their post-high school aspirations. Recommendations are made for school personnel. particularly counselors. to address high school students' career and lifestyle development needs from a contextual textual perspective.